2007
DOI: 10.1074/jbc.m609466200
|View full text |Cite
|
Sign up to set email alerts
|

Relative Sensitivity of Parkin and Other Cysteine-containing Enzymes to Stress-induced Solubility Alterations

Abstract: Loss of parkin function is a predominant cause of familial Parkinsonism. Emerging evidence also suggests that parkin expression variability may confer a risk for sporadic Parkinson disease. We have recently demonstrated that a wide variety of Parkinson disease-linked stressors, including dopamine (DA), induce parkin solubility alterations and promote its aggregation within the cell, a phenomenon that may underlie the progressive susceptibility of the brain to degeneration. The vulnerability of parkin to stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 22 publications
(36 reference statements)
7
60
0
Order By: Relevance
“…We found that HHARI is sensitive to oxidative stress-induced misfolding similarly to Parkin, which is in line with recent observations (33,36). However, the propensity to misfold upon C-terminal truncations was specific for Parkin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that HHARI is sensitive to oxidative stress-induced misfolding similarly to Parkin, which is in line with recent observations (33,36). However, the propensity to misfold upon C-terminal truncations was specific for Parkin.…”
Section: Discussionsupporting
confidence: 93%
“…Misfolding of Parkin induced by pathogenic mutations or cellular stress has been established as a major mechanism of Parkin inactivation, accentuating a possible pathological role of Parkin even in sporadic PD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(33)(34)(35). It is obvious that the high cysteine content found in the RBR domain predisposes Parkin to oxidative stress-induced inactivation and misfolding, a phenomenon that has recently been shown experimentally (36). Interestingly, in comparison to other RBR proteins Parkin seems to be uniquely sensitive to dopamine-induced inactivation (33,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A corollary of this conclusion is that the ARJP mutations C289G, C431F, and C441R found in the parkin RING1 and RING2 domains are also expected to be important zinc coordinating residues because our work shows that these domains each bind two zinc ions. These proteins and several other cysteine substituted parkin derivatives also form insoluble aggresomes consistent with disruption of zinc binding to the RING1, IBR, and RING2 domains (55,57). In particular, a C166A substitution caused increased aggregation and insolubility compared with wild type parkin consistent with a structural zinc-binding role in RING0 (57).…”
Section: Discussionmentioning
confidence: 88%
“…These proteins and several other cysteine substituted parkin derivatives also form insoluble aggresomes consistent with disruption of zinc binding to the RING1, IBR, and RING2 domains (55,57). In particular, a C166A substitution caused increased aggregation and insolubility compared with wild type parkin consistent with a structural zinc-binding role in RING0 (57).…”
Section: Discussionmentioning
confidence: 88%